2010
DOI: 10.1002/pits.20512
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Accelerated Reading with classwide interdependent group‐oriented contingencies

Abstract: An across-groups (classrooms), multiple-baseline design was used to investigate the effects of an interdependent group-oriented contingency on the Accelerated Reader (AR) performance of fourth-grade students. A total of 32 students in three classes participated. Before the study began, an independent group-oriented reward program was being applied (i.e., a student received access to a tangible reward after passing each AR comprehension test). This program was supplemented with an interdependent group-oriented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In addition, they may foster peer support and community in a classroom (Groves & Austin, 2019). This approach to motivation is especially suitable for use with a whole class of diverse learners and generally has demonstrated a positive impact on students' performance (Bowman-Perrot et al, 2013;Pappas et al, 2010;Rohrbeck et al, 2003).…”
Section: Ways To Motivate Students To Engage In Repeated Readingmentioning
confidence: 99%
“…In addition, they may foster peer support and community in a classroom (Groves & Austin, 2019). This approach to motivation is especially suitable for use with a whole class of diverse learners and generally has demonstrated a positive impact on students' performance (Bowman-Perrot et al, 2013;Pappas et al, 2010;Rohrbeck et al, 2003).…”
Section: Ways To Motivate Students To Engage In Repeated Readingmentioning
confidence: 99%
“…The variations of interdependent group-oriented contingencies, such as randomized reward schedules, have shown promise for spelling ) and math homework accuracy (Little et al 2010). Moreover, the researchers have shown that interdependent group-oriented contingencies may enhance the outcomes when combined with other academic interventions (e.g., Malone and McLaughlin 1997;Pappas et al 2010;Sharp and Skinner 2004).…”
Section: Group-oriented Contingenciesmentioning
confidence: 97%
“…5 Researchers who have examined the use of such external motivators to encourage children to read have noted that they either have no impact or a negative impact on children's motivation to read and that they can turn reading into a competition. 6 Finally, researchers have noted that when extrinsic motivators have proven to be successful, they are in the form of literacy incentives, in which books are given away as prizes for reaching a goal. 7…”
Section: Reading Motivation Theorymentioning
confidence: 99%